Cabo Branco Cliff – João Pessoa, PB: Geomorphological characterization and associated erosional processes - Pinheiro Maia, Rubson; Vidal Souza, Anna Sabrina; Ferreira Andrade, Antonia Beatriz (Revista Brasileira de Geomorfologia, 2025)
Several active coastal cliffs have been undergoing erosional processes that cause risks and may comprise public roads and the safety of the local population and tourists. A representative example of this situation is the Cabo Branco Cliff, in João Pessoa (PB), Brazil, which recently had rock armour was placed along the coastline as a measure to reduce the erosion. In view of this, this study aims to characterize and evaluate the retraction of the escarpment, considering factors such as the rock control of the Barreiras Formation and the effects of human interventions on the top (asphalt waterproofing) and base (rock armour) of the coastal cliff. A photogrammetric survey was carried out with a drone to generate a high-resolution digital surface model (DSM) (7 cm-resolution mesh). Geomechanical tests were performed with an analog rebound hammer in some sectors of the cliff. Physical resistance tests were also performed by measuring rebound values ​​with an analog rebound hammer. The fieldwork allowed a detailed description of erosion processes. The results indicate that the cliff's retrogradation is maintained due to persistent erosion by gravitational collapse. At present, the effectiveness of rock armour will be most noticeable in maintaining the talus deposits, since the top of the cliff will continue to recede, likely compromising even more public facilities installed there. In the long term, sea defense will be more effective in reducing the accelerated erosion of the cliff due to the change in profile and topographic gradient.